Comparison of the Fundamental Beliefs of the Seventh-day Adventist Church with Calvinist About the Sabbath, Food, Worship, and Predestination - Muntu, Donald Loffie (Fakultas Filsafat Universitas Advent Indonesia, 2024)
This study intends to examine the differences of the fundamental beliefs of the Seventh-day Adventist Church (SDA church) with Calvinism traditions about Sabbath, food, worship, predestination. This study concluded that SDA church's understanding or view with the Calvinism regarding the fundamental beliefs about the Sabbath concluded that the SDA church’s understanding is more biblical than the Calvinist tradition. SDA church belief on food is more biblical and the practice is in accordance with the Bible compared to the Calvinism. SDA church’ understanding or views and practices in worship with the Calvinism are almost practically the same in their procedures. SDA church’s understanding or view with the Calvinism regarding predestination differ in view, SDA church is the most in accordance with the Bible. SDA church has their beliefs and practices as well according to the Bible, while the Calvinism has an understanding or belief in accordance with the interpretation of church reformers such as John Calvin and other general church. This study suggests to both denominations regarding Sabbath, food, worship, and predestination to harmonize understanding based on the Bible so as not to increase or reduce the true understanding while there are similarities in implementing their worship. The Seventh-day Adventist church has biblical beliefs and their practices according to the Bible, while the Calvinist tradition has an understanding according to the interpretation of church reformers such as John Calvin and also the general church.